2020
DOI: 10.3390/jof6030099
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Quorum-Sensing Molecules: A Review of Their Antifungal Effect against Candida Biofilms

Abstract: The number of effective therapeutic strategies against biofilms is limited; development of novel therapies is urgently needed to treat a variety of biofilm-associated infections. Quorum sensing is a special form of microbial cell-to-cell communication that is responsible for the release of numerous extracellular molecules, whose concentration is proportional with cell density. Candida-secreted quorum-sensing molecules (i.e., farnesol and tyrosol) have a pivotal role in morphogenesis, biofilm formation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 111 publications
(165 reference statements)
2
44
0
3
Order By: Relevance
“…In the present paper, we explored the efficacy of the peptide towards the dualspecies Candida/Klebsiella biofilm, showing its ability of both inhibiting and eradicating in vitro the biofilm at sub-MIC concentrations. The low antimicrobial activity of the peptide used in this work towards C. albicans and K. pneumoniae was very low and was similar to that of other previously tested membranotropic peptides [14,15]; nevertheless, these characteristics may represent an advantageous property in the prevention of the possible development of resistances in the entire microbial consortium, a feature typical of several compounds proposed as anti-biofilms molecules [11]. The mechanism of action of gH625-M against C. albicans monospecies biofilm, as shown by a CSLM analysis previously reported [15], is initially directed towards the esopolymeric matrix of the biofilm and then penetrates across cell membranes, producing a local and temporary destabilization of membranes, which nonetheless has scarce effects on cell viability.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In the present paper, we explored the efficacy of the peptide towards the dualspecies Candida/Klebsiella biofilm, showing its ability of both inhibiting and eradicating in vitro the biofilm at sub-MIC concentrations. The low antimicrobial activity of the peptide used in this work towards C. albicans and K. pneumoniae was very low and was similar to that of other previously tested membranotropic peptides [14,15]; nevertheless, these characteristics may represent an advantageous property in the prevention of the possible development of resistances in the entire microbial consortium, a feature typical of several compounds proposed as anti-biofilms molecules [11]. The mechanism of action of gH625-M against C. albicans monospecies biofilm, as shown by a CSLM analysis previously reported [15], is initially directed towards the esopolymeric matrix of the biofilm and then penetrates across cell membranes, producing a local and temporary destabilization of membranes, which nonetheless has scarce effects on cell viability.…”
Section: Discussionsupporting
confidence: 68%
“…The potential use of antimicrobial peptides (AMPs) as a valid alternative to conventional antibiotics has been acknowledged and widely studied. In fact, their fast and strong antimicrobial activity, their antibiofilm action, and their reduced induction of resistance compared to conventional antibiotics make AMPs relevant compounds for controlling infections due to multi-drug resistant microorganisms embedded in a biofilm [10][11][12]. Among AMPs, there is a particularly relevant class of peptides, known as membranotropic peptides, which, apart from their eventual antimicrobial activity, present a high ability to disrupt the biofilm and thus may have an action both in the inhibition and in the eradication of the biofilm [13].…”
Section: Introductionmentioning
confidence: 99%
“…Alternative treatments interfering with quorum-sensing have recently become attractive therapeutic strategies, particularly against difficult-to-treat multidrug-resistant pathogens such as C. auris (9,(21)(22). Previous studies have reported that fungal quorum-sensing molecules may have a remarkable antifungal effect and/or a potent adjuvant effect in combination with traditional antifungal agents (7,10,23-26).…”
Section: Discussionmentioning
confidence: 99%
“…Although farnesol does not affect the growth rate of C. albicans when growing in planktonic form, it significantly decreased the growth of C. auris regarding both planktonic cells and also 1-dayold biofilms of this organism (7). Recently, alternative therapeutic approaches designed to disturb quorum-sensing have become an attractive treatment strategy (8)(9). The usage of farnesol and traditional antifungal drugs in combination may provide new insights into the management of newly emerged fungal species, such as C. auris, which poses a global threat to the nosocomial environment (7,10).…”
Section: Introductionmentioning
confidence: 99%
“…The reviews in this Special Issue covered recent developments in the area of Candida albicans sexual biofilms specifically focusing on how they are formed, their physical characteristics, and their role in Candida biology [13], the properties of the quorum sensing molecules farnesol and tyrosol secreted by Candida and their effect as anti-biofilm agents [14], and an extensive compilation of plant derived compounds with activities against biofilms of distinct Candida species [15]. Overall, this Special Issue is a great resource highlighting novel work on fungal biofilms.…”
mentioning
confidence: 99%